2016
DOI: 10.1108/ijhrh-10-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Mental health predicted by coping, social support, and resilience among young unwed pregnant Malaysian women and mothers living in shelter homes

Abstract: Purpose There is a dearth of research on unwed young pregnant Malaysian women and mothers’ coping strategy and resilience in the context of limited social support they received. Hence, the purpose of this paper is to investigate the prediction of mental health by coping, social support, and resilience among unwed young Malaysian pregnant women and mothers. Design/methodology/approach Quantitative data of two assessments from respondents aged 11 to 32 years during their stay in shelter homes have been analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Staying in residential facilities that prevent mothers from drinking and smoking does not necessarily decrease this risk. These findings are in agreement with a study showing that unwed mothers are more likely to consume alcohol and nicotine [ 43 , 44 , 45 ]. Prior studies suggest that frequent use of drug use and smoking is strongly related to early pregnancy, since habitual use is a sign of having difficulties in their life [ 13 , 16 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Staying in residential facilities that prevent mothers from drinking and smoking does not necessarily decrease this risk. These findings are in agreement with a study showing that unwed mothers are more likely to consume alcohol and nicotine [ 43 , 44 , 45 ]. Prior studies suggest that frequent use of drug use and smoking is strongly related to early pregnancy, since habitual use is a sign of having difficulties in their life [ 13 , 16 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…The two studies on partner emotional or affective support were primarily related to maternal health 45 46. Families and partners often reacted negatively by rejecting unwed pregnant teenagers or teenage mothers 46. These rejections were expressed differently, including avoiding pregnant teenagers or verbal abuse 46.…”
Section: Resultsmentioning
confidence: 99%
“…Families and partners often reacted negatively by rejecting unwed pregnant teenagers or teenage mothers 46. These rejections were expressed differently, including avoiding pregnant teenagers or verbal abuse 46. The analysis suggested that low-resilient women with threatened premature labour reported higher pressures from child support concerns after delivery, less active coping, less positive affect and more negative affect 45…”
Section: Resultsmentioning
confidence: 99%
“…If anyone got into trouble then the other neighbors would immediately help him according to his abilities. The people described social life with their family and friends, not just the fact that the participants had family and friends who could be invited to socialize well (Ebbers et al, 2015;Nor Jana et al, 2016). Social support from various social groups is one way to deal with stress (Liu et al, 2016;Poole et al, 2017).…”
Section: Relation Positive With Othermentioning
confidence: 99%